Algorithm-Architecture Matching for Signal and Image Processing Best papers from Design and Architectures for Signal and Image Processing 2007 & 2008 & 2009 - Gogniat, Guy.; Milojevic, Dragomir; Morawiec, Adam.; Erdogan, Ahmet; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Advances in signal and image processing together with increasing computing power are bringing mobile technology closer to applications in a variety of domains like automotive, health, telecommunication, multimedia, entertainment and many others. The development of these leading applications, involving a large diversity of algorithms (e.g. signal, image, video, 3D, communication, cryptography) is classically divided into three consecutive steps: a theoretical study of the algorithms, a study of the target architecture, and finally the implementation. Such a linear design flow is reaching its limits due to intense pressure on design cycle and strict performance constraints. The approach, called Algorithm-Architecture Matching, aims to leverage design flows with a simultaneous study of both algorithmic and architectural issues, taking into account multiple design constraints, as well as algorithm and architecture optimizations, that couldn$1 (Bt be achieved otherwise if considered separately. Introducing new design methodologies is mandatory when facing the new emerging applications as for example advanced mobile communication or graphics using sub-micron manufacturing technologies or 3D-Integrated Circuits. This diversity forms a driving force for the future evolutions of embedded system designs methodologies. The main expectations from system designers$1 (Bpoint of view are related to methods, tools and architectures supporting application complexity and design cycle reduction. Advanced optimizations are essential to meet design constraints and to enable a wide acceptance of these new technologies. Algorithm-Architecture Matching for Signal and Image Processing presents a collection of selected contributions from both industry and academia, addressing different aspects of Algorithm-Architecture Matching approach ranging from sensors to architectures design. The scope of this book reflects the diversity of potential algorithms, including signal, communication, image, video, 3D-Graphics implemented onto various architectures from FPGA to multiprocessor systems. Several synthesis and resource management techniques leveraging design optimizations are also described and applied to numerous algorithms. Algorithm-Architecture Matching for Signal and Image Processing should be on each designer$1 (Bs and EDA tool developer$1 (Bs shelf, as well as on those with an interest in digital system design optimizations dealing with advanced algorithms.s
Preface -- Part 1: Architectures for embedded applications -- Chapter 1: Architectures for image processing -- Chapter 2: Architectures for signal and telecommunication processing -- Part 2: Data acquisition and embedded systems -- Chapter 3: Sensors for data acquisition -- Chapter 4: Operators for embedded systems -- Chapter 5: Partial and dynamic reconfiguration for signal and image processing -- Part 3: Embedded systems design -- Chapter 6: RTOS for embedded systems -- Chapter 7: Scheduling of embedded systems -- Chapter 8: CAD tools for signal and image processing.
Keywords: Engineering; Computer science; Algorithms; Engineering; Signal, Image and Speech Processing; Processor Architectures; Algorithms